2017
DOI: 10.1002/14651858.cd003414.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Cycle regimens for frozen-thawed embryo transfer

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
228
2
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 267 publications
(242 citation statements)
references
References 79 publications
9
228
2
3
Order By: Relevance
“…There is limited published data available. Although the published studies identified on the subject differ somewhat in their conclusions, they support early FET after a stimulation cycle . Santos‐Ribiero et al .…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…There is limited published data available. Although the published studies identified on the subject differ somewhat in their conclusions, they support early FET after a stimulation cycle . Santos‐Ribiero et al .…”
Section: Introductionmentioning
confidence: 93%
“…Frozen embryo transfer is no longer seen as simply supplemental to fresh transfer and is more frequently being planned electively as evidence has accumulated of potential benefits of avoiding fresh transfer. This has been facilitated by improved cryopreservation techniques, including the use of vitrification and improved cycle preparation regimens for FET . Recognised benefits include improved implantation and pregnancy rates, and prevention of ovarian hyperstimulation syndrome …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently there is insufficient evidence to support the use of one cycle regimen in preference to another in preparation for FET in sub-fertile women with regular ovulatory cycles. 3 Luteinized unruptured follicle (LUF) is considered as one of the causes of subfertility. LUF is observed in 10% of natural menstrual cycles in fertile women, but in stimulated cycles it is higher.…”
Section: Introductionmentioning
confidence: 99%